Exploring the Effects of Hydrogen Peroxide on Biofilm Development and Antibiotic Susceptibility - Hwazen Amer Shnyoor; Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2024)
Hydrogen peroxide is one of the most important chemical compounds that affect the formation of biofilm of microorganisms and response to antimicrobial agents which can be used in war against pathogenic microorganisms in healthcare institutions. The current study aims to highlight the mechanism of the effect of H2O2 on biofilm formation, in addition to the possibility of using it to enhance the ability of antimicrobials to reduce the outbreak of infectious disease. In this review article, the impact of hydrogen peroxide on the susceptibility of pathogenic bacteria to antibiotics will be screened through the role of H2O2 in reducing biofilm formation. Here, the mechanism of the effect of H2O2 on the body of pathogenic bacteria through oxidation stress, eradication of biofilm, destruction of microbial membrane, and inhibition of microbial enzymes. The effect of hydrogen peroxide on biofilm formation depends on the concentration of hydrogen peroxide and the duration of exposure of microorganisms. In some time the low concentrations of H2O2 induce biofilm formation and high concentrations may reduce the biofilm formation (and that may be dependent on the species of microorganism). The effect of H2O2 on biofilm formation is through reducing initial attachment as well as interfering with the maturation and maintenance of biofilm. Hydrogen peroxide has an important role in enhancing antibacterial agents and this may contribute to redrawing the therapeutic strategy in the future. It can be concluded from the present study that H2O2 has a role in reducing the outbreak of infectious diseases and helps in enhancing the antibacterial war, which contributes to enhancing public health.
Keywords: Antibiotics, Bacterial susceptibility, Biofilm, Developing antibacterial agents, Hydrogen peroxide.